Determinants of Accident Status on Student Commuters of Jabodetabek in 2019 (Jurnal Matematika, Statistika dan Komputasi, 2021)
Traffic accidents among students are one of the problems experienced in the Greater Jakarta area. World Health Organization (WHO) stated that younger drivers are the most vulnerable group to experiencing traffic accidents, including the students. According to Badan Pusat Statistik (BPS), it was estimated that as many as 301,120 Jabodetabek commuters had experienced a traffic accident in 2019. Moreover, 13 to 14 out of the 100 commuters who had experienced traffic accidents are student commuters or commuters with the main activities going to school. Therefore, this study was conducted to determine the factors that affect the accident status of Jabodetabek student commuters in 2019 and their odds ratios by using the 2019 Jabodetabek Commuter Survey data. The analytical method used is a binary logistic regression with the parameter estimation method using penalized maximum likelihood estimation (PMLE). And the results showed that the variables of age, gender, last education, mode of transportation, classification of the area of residence, distance traveled, and the area of the activity had a significant influence on the accident status of Jabodetabek student commuters. Furthermore, student commuters who live in rural areas have the highest tendency to experience a traffic accident.
Keywords: traffic accident; commuter; student; binary logistic regression; Firth's method; Jabodetabek